Предмет: Алгебра, автор: Аноним

Плиззз срочно нужно!!!!
1)Упростите выражение
а)√3(√27-√48)
б) (√14-2)(2+√14)
в) (5√7-√63+√14)√7
г) (3√5+2√10)²               

Ответы

Автор ответа: irkarom
0
sqrt3(sqrt{27}-sqrt{48})=sqrt3(sqrt{9*3}-sqrt{16*3})=sqrt3(3sqrt3-4sqrt3)=\
=sqrt3(-sqrt3)=-3\
\

(sqrt{14}-2)(2+sqrt{14})=(sqrt{14})^2-2^2=14-4=10

(5sqrt7-sqrt{63}+sqrt{14})sqrt7=(5sqrt7-sqrt{9*7}+sqrt{2*7})sqrt7=\
=(5sqrt7-3sqrt{7}+sqrt{2}*sqrt{7})sqrt7=(2sqrt{7}+sqrt{2}*sqrt{7})sqrt7=\
=2*(sqrt7)^2+sqrt2*(sqrt7)^2=2*7+sqrt2*7=14+7sqrt2

(3sqrt5+2sqrt{10})^2=(3sqrt5)^2+2*3sqrt5*2sqrt{10}+(2sqrt{10})^2=\
=9*5+12sqrt{5*5*2}+4*10=45+12*5sqrt2+40=95+60sqrt2
Похожие вопросы